Evidence of Middle Holocene landslide-generated tsunamis recorded in lake sediments from Saqqaq, West Greenland - N. J. Korsgaard; K. Svennevig; A. S. Søndergaard; G. Luetzenburg; G. Luetzenburg; M. Oksman; N. K. Larsen (Natural Hazards and Earth System Sciences, 2024)
The Vaigat strait (Sullorsuaq) in West Greenland is well known for its susceptibility to landslides and historical landslide-generated tsunamis. Recent mapping of the seabed in the Vaigat strait has revealed several prehistoric giga-scale (volumes of 109 m3) tsunamigenic landslides. However, the timing of these giga-scale tsunamis is largely unconstrained, but they are assumed to have occurred after the last deglaciation. Here, we report on lake sediment core records from four coastal lakes located between 19 and 91 m above sea level (a.s.l.) on the Saqqaq foreland at the eastern end of the Vaigat strait. We use a multiproxy approach including X-ray fluorescence (XRF) and magnetic susceptibility core scanning along with a screening for marine diatoms to identify at least two tsunami deposits in two of the four sediment cores. Radiocarbon dating of aquatic macrofossils and bulk samples suggest that the tsunami events occurred at ca. 7.6 and 7.3 ka cal BP. Using a previously published relative sea level curve from Vaskebugt, Arveprinsen Ejland (Alluttoq), located 40 km southeast of Saqqaq, we infer wave runup heights of ca. 41–66 and 45–70 m, respectively, for the two tsunami events. These runup heights from prehistoric tsunamis are 1 to 2 orders of magnitude higher than the historic landslide-tsunami runup heights at Saqqaq which only reached an elevation of ca. 3 m in November 2000. While we found deposits from two tsunami events in the lake sediments, landforms from at least nine giga-scale landslides are present on the seafloor of Vaigat. We infer that these deposits probably represent the two most recent tsunamis identified in the Vaigat strait and that the older tsunamis must have happened between the last deglaciation and the oldest sediment in the lakes, i.e., between ca. 10.0 and 8.5 ka cal BP.